1995
DOI: 10.1243/pime_proc_1995_209_067_02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TIG Welding Arc Using Boundary-Fitted Coordinates

Abstract: The characteristics of argon arc in tungsten inert gas (TIG) welding have been studied by considering the electrode shape which has an effect on the current density distribution near the electrode tip. For including the electrode surface configuration into the solution domain, the boundary-fitted coordinate system was employed. Then, a non-rectangular computational region in the physical domain was transformed into a rectangular area with uniformly spaced grids in the computational domain using the second-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…The maximum shear stress was found to occur 1 mm from the arc centreline; and for argon and helium this was found to be ~80 N/m 2 and ~240 N/m 2 respectively. For argon, this was in agreement with data published by Lee and Na [14] and Hu and Tsai [15] for GTAW and GMAW respectively. The results show that helium produces a considerably larger plasma shear stress, thus encouraging the liquid weld metal to flow radially outwards at the weld pool surface.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The maximum shear stress was found to occur 1 mm from the arc centreline; and for argon and helium this was found to be ~80 N/m 2 and ~240 N/m 2 respectively. For argon, this was in agreement with data published by Lee and Na [14] and Hu and Tsai [15] for GTAW and GMAW respectively. The results show that helium produces a considerably larger plasma shear stress, thus encouraging the liquid weld metal to flow radially outwards at the weld pool surface.…”
Section: Resultssupporting
confidence: 92%
“…The benefits of using alternating shielding gases are linked to three independent phenomenon [1]: a) variation in arc pressure, b) arc pressure peaking and c) variation in weld pool fluidity, and are said to result in flow vectors opposite in direction for argon and helium [2]. Arc pressure measurements conducted when using argon have been published whilst investigating the effects of a variety of welding parameters including welding current [7][8][9][10][11], tungsten electrode geometry [10][11][12], arc length [10], nozzle outlet diameter [13] and shielding gas pressure [13]. The shielding gas composition is also known to have a considerable effect on the arc pressure [9,10], however, the availability of data for helium and argon-helium mixtures is extremely limited and that for alternating shielding gases is non-existent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For argon, this was in agreement with data published by Lee and Na [14] and Hu and Tsai [15] for GTAW and GMAW respectively. The results show that helium produces a considerably larger plasma shear stress, thus encouraging the liquid weld metal to flow radially outwards at the weld pool surface.…”
Section: Resultssupporting
confidence: 92%
“…Studies [5][6][7] have shown that the current density increases approximately linearly with increasing current, while Fan and Shi 8 stated that the electromagnetic force is the driving force for fluid flow in the arc plasma and increases with increasing current density; thus the electromagnetic force will increase with increasing arc pressure.…”
Section: Introductionmentioning
confidence: 99%